Elucidating the oxygen electrocatalytic activity of chromium cobalt spinel oxide supported over the spherical carbon for rechargeable zinc-air batteries - Kurian, Maria; Amin, Seerat; Pandikassala, Ajmal; Manoj, Malavika; Vijayan, Jubina; Krishnamurty, Sailaja; Kurungot, Sreekumar (Batteries & Supercaps, 2026)
Cr1.5Co1.5O4 spinel nanoparticles supported over 3D spherical carbon (Cr1.5Co1.5O4/C-800) is synthesized as a bifunctional electrocatalyst for oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) for rechargeable zinc air battery (RZAB) applications. The incorporation of Cr into the spinel lattice and the decoration of the active material on a 3D spherical carbon support with intrinsic ORR activity and superior electrical conductivity enable uniform distribution of catalytically active sites, thereby improving bifunctional catalytic activity. The DFT studies were conducted to understand the role of the Cr in modulating the catalytic sites of the active material and to elucidate its effect on tuning the Co sites to enhance the activity. Half-cell studies show that Cr incorporation and spherical carbon support synergistically enhanced catalytic activity, with the Cr1.5Co1.5O4/C-800 catalyst demonstrating an onset potential of 0.93 V (70 mV lower than Pt/C) and an E & half; value of 0.70 V for ORR and an overpotential of 0.369 V at 20 mA cm-2 (eta 20) for OER (0.375 V for the RuO2 catalyst). The catalyst's bifunctional activity was validated in an RZAB, where it outperformed the Pt/C-RuO2 benchmark, delivering superior rate capability and stability and achieving a cycling life exceeding 145 h.
Keywords: chromium cobalt spinel oxide; Oxygen Evolution Reaction; oxygen reduction reaction; rechargeable zinc-air battery